Challenges of building digital repositories in Africa: A case study of best practise - Bakhoum, Nafissatou (Dakar, Senegal, 2016)
Libraries are known to promote change through individual and institutional capacity leading to quality, effectiveness and then to development. Information and knowledge, as a vehicle of power and wealth, are then likely to root out economic marginalization, inequalities, unemployment and other shortages the African continent is suffering. But, in spite of its outstanding scholarly and cultural heritage and huge progress made in ICT, it is striking that Africa is still lagging behind in the international scheme of knowledge production, which is conducting the world. Deficiencies in education, lack of innovation, of a wide professional militantism and of a strong political commitment are the main causes. African libraries, therefore become conscious that such weaknesses, instead of being experienced as an additional source of frustration can be turned into an impulse for innovative change. Even if federating exhaustively valuable African contents in a unique virtual space, has not already become a reality, some African scientific institutions step boldly forward in implementing programs to meet the huge challenge of digitizing scholarly contents and providing online access to them. They are struggling to break with a long period of gathering rich scientific materials, formerly shelved in libraries as treasures, in order to safeguard and valorize them. Then, building digital repositories and promoting open access in a context with limited resources has never been so relevant. They have proven efficient in providing technical infrastructure, quality-based and value-added solutions to the management of collections, especially in heritage libraries. The objective of this paper is to reinforce, through demonstration, the optimistic view consisting of believing that all is not bleak in Africa, and overcoming challenges depends on how being strategic in addressing core issues. It focuses on two points: 1. Challenges attached to the preservation and valorization of African scholarly contents; After presenting briefly the context of accumulation of scientific materials in Africa, namely in Afrique occidentale française (AOF), we focus on the benefit effects of digitizing African scholarly contents and how it can impact on the dissemination of research outputs and sustainable development. 2. Promoting access through a digital repository: a case study of best practice. This part is demonstrative and illustrates that some African academic institutions adapt to innovative change and develop capacities to build worth institutional repositories. This case study is from Institut fondamental d’Afrique noire Cheikh Anta Diop (FAN Ch A Diop).
Keywords: African digital libraries; heritage libraries; Digitization; Digital repository; Open access; ICT; Sustainable development; IFAN Ch A Diop; Senegal; Africa